A literature kit for Criss cross - Reed, Nat, 1950- (Literature kit., 2012)
In this State Standards-aligned Literature Kit™, we divide the novel by chapters or sections and feature reading comprehension and vocabulary questions. In every chapter, we include Before You Read and After You Read questions. The Before You Read activities prepare students for reading by setting a purpose for reading. They stimulate background knowledge and experience, and guide students to make connections between what they know and what they will learn. The After You Read activities check students' comprehension and extend their learning. Students are asked to give thoughtful consideratio.